Peran Keluarga Multikultural dalam Pembentukan Toleransi dan Karakter Religius Anak - Sofiana Nur Ramadani; Muh. Sabilar Rosyad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to examine the role of multicultural families in shaping tolerance, respect for differences, and religious character of children in Kuprik Village, South Papua. The main focus of this research is on family strategies in internalising values, socialisation mechanisms applied, and values constructed in the daily practices of cross-cultural and religious families. The method used is a qualitative approach with an ethnographic design, through participatory observation, in-depth interviews, and documentation of eight families with different cultural and religious backgrounds. The results showed that multicultural families actively in still tolerance values through direct experience, behavioural role models, and open communication in the household environment. In addition, they build respect for diversity and develop children's religious character based on universal values such as honesty, compassion and responsibility. The findings confirm that the family as the main socialisation agent has an important role in fostering positive attitudes and religious character in a plural society. This research contributes to the development of character education theory, family sociology and multicultural studies by providing a contextualised understanding of parenting practices in cross-cultural families.